2010
DOI: 10.1111/j.1471-0528.2010.02578.x
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery embolisation combined with local methotrexate for treatment of caesarean scar pregnancy

Abstract: Objective The aim of the study was to determine the efficacy of uterine artery embolisation (UAE) combined with local methotrexate (MTX) for the treatment of caesarean scar pregnancy, compared with other traditional modalities, and to investigate the complications associated with this treatment.Design A retrospective cohort study.Setting A large obstetrics and gynaecology unit within a university hospital in China.Sample Women who were diagnosed with a caesarean scar pregnancy between January 2003 and December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 25 publications
1
85
1
8
Order By: Relevance
“…Only three women were successfully treated without severe complications and with preservation of the uterus; the other eight women were treated with hysterectomy or wedge excision of the uterus. 18 In the present study, all the patients in group B were successfully treated with BUACE and did not require more invasive surgical procedures.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Only three women were successfully treated without severe complications and with preservation of the uterus; the other eight women were treated with hysterectomy or wedge excision of the uterus. 18 In the present study, all the patients in group B were successfully treated with BUACE and did not require more invasive surgical procedures.…”
Section: Discussionmentioning
confidence: 70%
“…The dose (100 mg/m 2 ) was higher than that previously reported in the literature. 18 Use of a higher dose speeds up the necrosis of the gestational sac, enabling complete resolution to occur before the gelfoam particles are absorbed. The uterine artery was embolized immediately after MTX infusion using gelfoam particles to maintain a relatively high local MTX concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, such countries need to acquire knowledge about new targets for effective treatment. The UAE technique used in association with intra-arterial MTX infusion was first described by Yang et al [9]. Their intention was to infuse the chemotherapy through the uterine arteries and not directly into the gestational sac or surrounding endometrium, which could cause scar rupture and extensive hemorrhaging.…”
Section: Discussionmentioning
confidence: 99%
“…Strict imaging criteria must be used in performing the diagnosis-an empty uterus, empty cervical canal, development of the sac in the anterior part of the isthmic portion and an absence of healthy myometrium between the bladder wall and the gestational sac. A retrospective cohort study was done in University hospital in China to determine the efficacy of Uterine Artery Embolisation (UAE) combined with local Methotrexate (MTX) for the treatment of Caesarean scar pregnancy between Jan 2003 and Dec 2008 and they concluded that UAE with local MTX is of benefit to women wishing to preserve fertility, and is suitable for use as a primary treatment of caesarean scar pregnancy 26 . Because of difficult diagnosis and probably delayed treatment this patient developed complication resulting extended surgery with loss of fertility.…”
Section: Discussionmentioning
confidence: 99%